Engine Power Plant Design Considering Grid Fault Tolerance - Suikkanen, Anna (My University, 2020)
The compliance requirements of the power plants are getting more complex due to the strict grid code requirements. The power supply to the grid needs to be secured during faults in the grid and it is implemented with correct protection settings and equipment selection in the plant. The objective is to sustain the fault and during that time the plant needs to be stable. The protection equipment and control system need to be designed to sustain the fault. The scope of this study is to analyse the design of the power plant control and its auxiliary systems and their behaviour during a three phase fault in the grid at HV side. The systems that are being studied are HV, MV and LV systems. These systems include plant control system and plant auxiliaries, power and station transformers and the process in a power plant. The power plant needs to remain stable, stay connected and withstand to the disturbances from the grid as required in various grid codes. Getting the result requires checking the parameters of the critical components in the studied systems and comparing them to the requirements of the grid. The objective of this study is to choose the correct design of the power plant auxiliaries. If the requirements don’t meet there is a risk that the power plant will disconnect from the grid. The parameters and requirements should be met also in the worst case. The components need to be changed if the critical elements fuel, water and air are being interrupted. The results have been gathered by checking the data sheets of the critical components and comparing them to the requirements of the grid codes. Simulations have also been made on HV, MV and LV systems to see how the fault affects the voltages and the frequency in the power plant. The studied fault is a three phase fault occurring in the HV side of the grid. The duration of the fault is 300 ms. The fault drops the voltage to zero at HV system but according to the simulations there are still approximately 0.26 pu of voltage remaining in the MV and LV systems because of a step-up transformer between the HV and MV system. The outcome of this thesis describes the status of all design (HV, MV, LV and auxiliary systems) of the power plant. Every system components and the purpose of its control and its suitability to withstand during the fault is studied and listed. The study provides some corrective and improved measures about the component selection criteria and the source of control power AC, DC and UPS. It is recommended to use UPS to stabilize the control voltage or move the critical components behind DC supply and use it with battery back-up. The transient situations don’t have an effect on the DC supply as they do in the AC supply.

Voimalaitosten vaatimukset muuttuvat monimutkaisemmiksi tarkkojen verkkosääntöjen vaatimusten vuoksi. Voimalaitoksen tehonsyöttö verkkoon on turvattava verkkovikojen aikana suojalaitteilla. Suojalaitteet, kuten releet, estävät voimalaitoksessa olevien sähkölaitteiden vaurioitumisen vikatilanteessa, jossa on uhka äkillisille jännitteenvaihteluille. Tämän tutkimuksen tavoitteena on analysoida voimalaitoksen ohjaus- ja apujärjestelmien suunnittelua ja järjestelmien toimintaa verkon suurjännitepuolella tapahtuvan kolmivaihevian aikana. Tutkittavana ovat suurjännite-, keskijännite- ja pienjännitejärjestelmät. Ne sisältävät laitoksen ohjausjärjestelmän, apujärjestelmät, tehomuuntajat, asemamuuntajat sekä voimalaitoksen prosessit. Voimalaitoksen täytyy olla vakaa ja kestää verkossa syntyviä vikoja. Voimalaitos ei saa irrota verkosta vian aikana. Tuloksen saaminen vaatii tutkittujen järjestelmien kriittisten komponenttien parametrien tarkistamista ja niiden vertaamista vaatimuksiin. Jos vaatimukset eivät täyty, vaarana on, että voimalaitos irtoaa verkosta. Parametrien tulisi täyttää vaatimukset myös ääritapauksessa. Voimalaitosten kriittisten elementtien eli polttoaineen, veden ja ilman syöttö ei saa keskeytyä. Tutkimuksen tulokset on saatu tarkistamalla kriittisten komponenttien tietolomakkeet, joiden tietoja on verrattu verkkokoodien vaatimuksiin. Voimalaitoksen toiminta vikatilanteessa myös simuloitiin, jotta nähtäisiin suurjännite-, keskijännite- ja pienjännitejärjestelmien jännitteen käyttäytyminen vikatilanteessa ja vian vaikutus taajuuteen. Työssä tutkittu vika on kolmivaiheinen ja tapahtuu verkossa suurjännitepuolella. Vian kesto on 300 ms. Vika pudottaa jännitteen nollaan voimalaitoksen suurjännitejärjestelmässä, mutta simulaation mukaan keski- ja pienjännitejärjestelmissä on edelleen 0.26 pu jännitettä. Tämä johtuu suur- ja keskijännitejärjestelmien välissä olevasta jännitteennostomuuntajasta. Tämän tutkimuksen tulokset kuvaavat voimalaitoksen laitteistojen (suurjännite-, keskijännite- ja pienjännitejärjestelmien sekä apulaitteiden) tilan. Työssä on tutkittu ja lueteltu kaikkien järjestelmien osat ja niiden ohjauksen tarkoitus. Laitteistojen osien sietokyky kolmivaiheisen vian aikana ja osien soveltuvuus on myös selvitetty. Tutkimus tarjoaa tarkennuksia ja parannusehdotuksia komponenttien valintakriteereihin ja ohjausjännitteen tehon syötön lähteeseen. On suositeltavaa käyttää UPS:ää vakauttamaan ohjausjännite tai siirtää kriittiset komponentit niin, että syöttö tapahtuu tasavirralla. Lisäksi syöttö kannattaa varmistaa akuilla. Jännitteen vaihtelut eivät vaikuta yhtä paljon tasavirtasyöttöön samoin kuin ne vaikuttavat vaihtovirtasyöttöön.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|